Regulation of inhibin/activin expression in rat early antral follicles - Andreone, Luz (2009)
The aim of the present study was to determine the endocrine activity of cultured early antral follicles (EAF) isolated from prepubertal diethylstilbestrol-treated rats. The effect of steroidogenic substrates and FSH on steroid, inhibin A and B, Pro-αC and activin A production was evaluated. Androsterone was the predominant steroid produced by EAF. The addition of androstenedione, androstenedione + FSH and progesterone stimulated oestradiol production, whereas 25-hydroxycholesterol (25-OH-Chol) increased progesterone production. Inhibin A, B, Pro-αC, and activin A were produced under basal conditions. The predominance of inhibin B over inhibin A was not affected by the addition of androstenedione or progesterone. Inhibin A and activin A production was stimulated by FSH. 25-OH-Chol increased Inha, Inhba and Inhbb mRNA expression and the production of the three molecular forms of inhibins but decreased activin A production. These results show that FSH and the steroid follicular microenvironment differentially modulate the gene expression of inhibin/activin subunits, their assembly and secretion.